Terahertz Transmission Characteristics of Free-Standing Fractal Jesus-Cross Structure - Xiong, Ri-Hui; Li, Jiu-sheng (Frontiers in Physics, 2020)
We have fabricated Jesus-cross structure on aluminum foil by using the femtosecond laser technique. By using terahertz time-domain spectroscopy (THz-TDS) system, the transmission properties of free-standing double-layer crossing fractal structure are tested. The parameters of the proposed structure were optimized by using finite element frequency domain technology of commercial software CST Microwave Studio package. The dimensions of the aluminum foil periodically patterned with crossing fractal structure are 1.5×1.5cm2. The resonant frequencies of the proposed structure are 0.216THz and 0.735THz with 3-dB bandwidths of 62GHz and 15GHz, respectively. The transmission ratio can reach to 0.89 and 0.57. It indicates the structure having dual-band filtering performance. This work has the potential to open a new avenue as a filter working for free-space terahertz radiation.